Muscle expression of SOD1G93A triggers the dismantlement of neuromuscular junction via PKC-Theta - Dobrowolny, Gabriella; Rudolf, Rüdiger (Antioxidants & redox signaling, 2018)
Aim: Neuromuscular junction (NMJ) represents the morphofunctional interface between muscle and nerve. Several chronic pathologies such as aging and neurodegenerative diseases, including muscular dystrophy and amyotrophic lateral sclerosis, display altered NMJ and functional denervation. However, the triggers and the molecular mechanisms underlying the dismantlement of NMJ remain unclear.Results: Here we provide evidence that perturbation in redox signaling cascades, induced by muscle-specific accumulation of mutant SOD1G93A in transgenic MLC/SOD1G93A mice, is causally linked to morphological alterations of the neuromuscular presynaptic terminals, high turnover rate of acetylcholine receptor, and NMJ dismantlement. The analysis of potential molecular mechanisms that mediate the toxic activity of SOD1G93A revealed a causal link between protein kinase Cθ (PKCθ) activation and NMJ disintegration.Innovation: The study discloses the molecular mechanism that triggers functional denervation associated with the toxic activity of muscle SOD1G93A expression and suggests the possibility of developing a new strategy to counteract age- and pathology-associated denervation based on pharmacological inhibition of PKCθ activity.Conclusions: Collectively, these data indicate that muscle-specific accumulation of oxidative damage can affect neuromuscular communication and induce NMJ dismantlement through a PKCθ-dependent mechanism. Antioxid. Redox Signal. 28, 1105-1119.
Gesehen am 04.04.2018